3 - La modernité mauritanienne: Enjeux difficiles d’une quête de citoyenneté: DOI: 10.4314/ad.v29i4.22206 - N'Gaïde Abderrahmane (Africa Development, 2004)
Building a homogenous and modern nation, a community of citizens within a sovereign state is a problematic issue in Africa. Everywhere, any attempt to achieve this has resulted in internal conflicts and devastation. Political and social actors have failed to overcome their parochial politics and build a national project, to which all citizens could identify. The creation of Mauritania is the evidence of the shortcomings of the colonial political projects. It was created to serve as a buffer state. It was structured from a conglomeration of peoples whose internal organisations and way of life are completely different. Ever since, any attempt to build a modern nation is confronted with both the complexity of the issues at stake and the complexity of the struggles for control of the political and economic spheres and even, of people. Increasingly, there are more and more virulent contestations which are reflected in everyday behaviours and are at the basis of identity fantasies. Inter-communal conflicts dominate the political and social scene; the needs for visibility of the social communities lead to constant and violent clashes, on a regular basis. To me, this reality is what Mauritanian modernity is all about. In my contribution, I attempt to describe this never ending and plural conflict.